Ecological signal in the size and shape of marine amniote teeth. Issue 1982 (14th September 2022) - Fischer, Valentin; Bennion, Rebecca F.; Foffa, Davide; MacLaren, Jamie A.; McCurry, Matthew R.; Melstrom, Keegan M.; Bardet, Nathalie
Abstract : Amniotes have been a major component of marine trophic chains from the beginning of the Triassic to present day, with hundreds of species. However, inferences of their (palaeo)ecology have mostly been qualitative, making it difficult to track how dietary niches have changed through time and across clades. Here, we tackle this issue by applying a novel geometric morphometric protocol to three-dimensional models of tooth crowns across a wide range of raptorial marine amniotes. Our results highlight the phenomenon of dental simplification and widespread convergence in marine amniotes, limiting the range of tooth crown morphologies. Importantly, we quantitatively demonstrate that tooth crown shape and size are strongly associated with diet, whereas crown surface complexity is not. The maximal range of tooth shapes in both mammals and reptiles is seen in medium-sized taxa; large crowns are simple and restricted to a fraction of the morphospace. We recognize four principal raptorial guilds within toothed marine amniotes (durophages, generalists, flesh cutters and flesh piercers). Moreover, even though all these feeding guilds have been convergently colonized over the last 200 Myr, a series of dental morphologies are unique to the Mesozoic period, probably reflecting a distinct ecosystem structure.